The effect of SPEOS method and music therapy on breastmilk production in primipara postpartum mothers - Titik Setyawan; Maya Erisna; Ida Ariyanti; Sri Wahyuni (Alma Ata University Press, 2021)
Background: Breastmilk production on the 2nd to 3rd day after delivery is still low and it can lead to breastfeeding adequacy problem. Hormonal constitute one of many factors that causing this condition. Therefore, there is a need for non-pharmacological interventions to increase breastmilk production in primpipara postpartum mothers. Objectives: The purpose of the study was to determine the effect of the SPEOS method (stimulation of endorphins, oxytocin, and suggestive massage) and classical music therapy on breastmilk production in primipara postpartum mothers. Methods: This study was a quasi-experiment with pretest and post-test with control group design. A total of 34 postpartum mothers from the first day to the fourth day were selected in this study randomly and were divided into an experimental group (EG) and control group (CG). Wilcoxon and Mann Whitney test was used for statistical analysis. Results: The average breastmilk production after the administration of the SPEOS method and music therapy interventions was increased significantly from 4.35 ml to 46.66 ml (p=0.0001) compared to control group 5.48 ml to 19.07 ml (p=0.0001). Conclusions: The combination of the SPEOS method and music therapy is effective in increasing breastmilk production in primipara postpartum mothers.